2013 IEEE International Conference on Communications Workshops (ICC) 2013
DOI: 10.1109/iccw.2013.6649205
|View full text |Cite
|
Sign up to set email alerts
|

Direction of arrival estimation with arbitrary virtual antenna arrays using low cost inertial measurement units

Abstract: In this paper, we have investigated the use of virtual antenna arrays at the receiver to do single antenna direction-ofarrival estimation. The array coordinates are obtained by doing simple dead reckoning using acceleration and angular speed measurements from a low cost micro-electro-mechanical system inertial measurement unit (IMU). The proposed solution requires no extra hardware in terms of receiver chains and antenna elements. Direction-of-arrival estimation results are obtained using a high resolution SAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Super-resolution techniques such as CLEAN [23], MUSIC [24], ESPRIT [25], SAGE [26], RiMAX [27] (to name a few) can obtain angular resolution beyond the inherent beamwidth of the antennas, but require phase coherence across the array elements. While phase drift can be tolerated and somewhat mitigated at microwave to achieve reasonable accuracy [28]- [30], even the best Rubidium (Rb) clocks (which are state-of-the-art for synchronization between the T and R) have short-term clock drift rate of 1-2 ns/min [31], tantamount to phase drift of more than one cycle at 60 GHz for a scan duration just 1 s. The phase drift is exacerbated at mmWave due to much longer scan durations resulting from larger array sizes (or equivalent narrower beams), typically a few elements at microwave but easily in the hundreds at mmWave in order to synthesize high gain [32]. Even for shorter durations, spikes up to 4 ns in clock drift have been observed from non-fluid motion when one end of the sounder is mobile [31].…”
Section: Introductionmentioning
confidence: 99%
“…Super-resolution techniques such as CLEAN [23], MUSIC [24], ESPRIT [25], SAGE [26], RiMAX [27] (to name a few) can obtain angular resolution beyond the inherent beamwidth of the antennas, but require phase coherence across the array elements. While phase drift can be tolerated and somewhat mitigated at microwave to achieve reasonable accuracy [28]- [30], even the best Rubidium (Rb) clocks (which are state-of-the-art for synchronization between the T and R) have short-term clock drift rate of 1-2 ns/min [31], tantamount to phase drift of more than one cycle at 60 GHz for a scan duration just 1 s. The phase drift is exacerbated at mmWave due to much longer scan durations resulting from larger array sizes (or equivalent narrower beams), typically a few elements at microwave but easily in the hundreds at mmWave in order to synthesize high gain [32]. Even for shorter durations, spikes up to 4 ns in clock drift have been observed from non-fluid motion when one end of the sounder is mobile [31].…”
Section: Introductionmentioning
confidence: 99%
“…In synthetic aperture navigation (SAN), the antenna movement can be uniform or arbitrary. In a uniform movement, computationally low-cost approaches (e.g., multiple signal classification (MUSIC) or estimation of signal parameters via rotational invariance techniques (ESPRIT)) can be used to estimate the direction-of-arrival (DOA) [30,31], whereas computationally expensive algorithms (e.g., space-alternating generalized expectation-maximization (SAGE)) must be used to estimate the DOA in an arbitrary movement [32]. Uniform structures require a bulky hardware platform, and the performance of arbitrary structures depends on the accuracy of the antenna location, which depends on the accuracy of the inertial measurement unit (IMU).…”
Section: Introductionmentioning
confidence: 99%
“…The array is formed using a single antenna element that is moved to different locations to form a so-called virtual antenna array. An inertial measurement unit (IMU) can be used to track the antenna positions as shown in [1], [2], where it has also been demonstrated that DoA estimation can be performed using such virtual antenna arrays. Since the antenna position is estimated from IMU measurements which are corrupted by noise, the antenna positions are known with an uncertainty associated with each antenna location.…”
Section: Introductionmentioning
confidence: 99%